THE EFFECT OF THE CONTRIBUTION OF LOCAL TAXES, LOCAL ORIGINAL INCOME, REGIONAL LEVIES AND TAX REVENUE SHARING ON REGIONAL SPENDING WITH ECONOMIC GROWTH AS A MODERATING VARIABLE GOVERNMENT AND DISTRICT GOVERNMENT - Asih, Surya (Accounting and Business Journal; Vol 1 No 2 (2019): ACCOUNTING AND BUSINESS JOURNAL, 2019)
The purpose of this study is to examine and determine the effect of local tax contributions, local ownsource revenues, regional user fees and tax revenue-sharing on regional spending with economic growth as a moderating variable. The approach in this study uses the associative approach Moderating Regression Analysis (MRA) where this study wants to test the influence of independent variables and test moderating variables. The target population in this study is the report on the realization of regional income of North Sumatra Province totaling 33 City Regencies. Data collection techniques using documentation studies from APBD reports. Data analysis techniques using multiple regression and moderating test. Multiple regression was performed to test simultaneously (F test) and partial (t test), while the moderating test used Residual test. simultaneously on Regional Expenditures. Partial test results can be proven that the Regional Tax Contribution significant effect on Regional Spending in North Sumatra Province. Locally-generated revenuesignificant effect on Regional Spending in North Sumatra Province. Regional Retribution significant effect on Regional Spending in North Sumatra Province. Tax Results no significant effect on Regional Spending in North Sumatra Province. The results of the moderating regression analysis (MRA) test can be concluded that economic growth is not a moderating variable that strengthens or weakens the relationship between Contribution of Regional Taxes, Regional Original Revenue, Regional Retribution and Tax Sharing on Regional Spending in the Province of North Sumatra